Proceedings of the Thirty-First International Joint Conference on Artificial Intelligence 2022
DOI: 10.24963/ijcai.2022/9
|View full text |Cite
|
Sign up to set email alerts
|

Achieving Envy-Freeness with Limited Subsidies under Dichotomous Valuations

Abstract: We study the problem of allocating indivisible goods among agents in a fair manner. While envy-free allocations of indivisible goods are not guaranteed to exist, envy-freeness can be achieved by additionally providing some subsidy to the agents. These subsidies can be alternatively viewed as a divisible good (money) that is fractionally assigned among the agents to realize an envy-free outcome. In this setup, we bound the subsidy required to attain envy-freeness among agents with dichotomous valuations, i.e., … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Goko et al (2022) showed that when the utilities are submodular functions with binary marginals, a total subsidy payment of n − 1 suffices. Subsequently, Barman et al (2022) showed that for general set valuations with binary marginals total subsidy payment of n − 1 suffices.…”
Section: Indivisible Goods With Subsidymentioning
confidence: 99%
“…Goko et al (2022) showed that when the utilities are submodular functions with binary marginals, a total subsidy payment of n − 1 suffices. Subsequently, Barman et al (2022) showed that for general set valuations with binary marginals total subsidy payment of n − 1 suffices.…”
Section: Indivisible Goods With Subsidymentioning
confidence: 99%
“…The budgeted maximin share allocation problem is also closely related to relaxed envy free allocation with budget constraints [8,9,19,21,30] . Other related results can be found in the recent surveys [4,23].…”
Section: Related Workmentioning
confidence: 99%
“…Since RG 0 ⊇ RG 1 ⊇ • • • ⊇ RG, by (9), there must exist an iteration τ , such that v ′ i (A(RG t , i)) ≥ β for each t ∈ {0, 1, . .…”
Section: Polynomial-time Algorithmmentioning
confidence: 99%